The Effect of Erigo's Brand Image on Buying Interests of Student - Endah Tri Hastuti; Naimatussaufafida Ardia Liyahana; Savira Aulia Fadhilah (APLIKATIF: Journal of Research Trends in Social Sciences and Humanities, 2023)
There are several factors that affect consumers' buying interest in a product or service. One of the factors is the brand image of a company. Communication activities are carried out by an enterprise to build a strong and positive brand image. Therefore, the purpose of this study is to find out whether Erigo's brand image has an influence on the buying interest of FIKOMM UMBY Student class of 2021. The population in this study was student of the Communication Science Study Program, Mercu Buana University Yogyakarta class of 2021 who came from the regular morning class of 226 Student, while the research sample used the Isaac and Michael sampling technique as many as 139 Student. Data collection uses a questionnaire containing statements related to brand image and buying interest. This research uses a type of quantitative research with mixed methods. The research data that has been obtained is then analyzed using SPSS software. The results showed that Erigo's brand image had an influence on the buying interest of FIKOMM UMBY Student class of 2021. The magnitude of the influence was 20.6%, so that other factors as much as 79.4% were influenced by other variables that were not studied.